Guided Demonstration Method to Improve Students' Skills in Processing Banana - Widagdo, Andika Kuncoro; Handajani, Sri; Astuti, Nugrahani; Aini, Annisa Nur; Yuliana, Siti; Bahar, Asrul (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2023)
This research describes the training process and results of banana processing through the demonstration method at MAN 2 Madiun. This research aims 1) to know the instructor's activities, 2) to find out the participants' activities, 3) to determine student learning outcomes, and 4) to find out the participants' responses to the training. This study used an experimental method with a pre-experimental research design model of a one-shot case study, observation as data collection techniques, and knowledge and skill tests. The process is documented. The research results are as follows: 1) The instructor's activities cover three aspects, namely the preliminary activity aspect, the core activity aspect, and the closing activity aspect, with a percentage result of 95%, which is included in the